The effects of chilling and freezing temparatures on the shelf-life of fresh shucked oysters. - Diaz, Rosario G. (College of Fisheries, University of the Philippines, 1976)
This study reports on the determination of a satisfactory "shelf-life" for shucked oyster meats stored at chilling and freezing temperatures. As part of the experiment, two groups composed of seven lots each of individually packed oyster meats were subjected to chilled and frozen storage in order to determine whether such temperatures will prevent or at least temporarily arrest quality deterioration for a definite length of time. At designated sampling intervals for each group, the samples were subjected to bacterial analysis (total plate count and determination of fecal coliforms) and organoleptic assessment (general acceptability, color, odor, appearance including factors like discoloration and presence of "colored" oysters). Samples at chilled storage showed a rapid deterioration in quality as judged compared with samples at frozen storage. Corollary to this experiment, pH of the samples were taken with the use of a Beckman Zeromatic pH Meter to determine the significance of chilled and frozen oyster samples.